2015
DOI: 10.1103/physreve.92.053002
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic correlations in shear flow: Multiparticle-collision-dynamics simulation study

Abstract: The nonequilibrium hydrodynamic correlations of a Multiparticle-Collision-Dynamics (MPC) fluid in shear flow are studied by analytical calculations and simulations. The Navier-Stokes equations for a MPC fluid are linearized about the shear flow and the hydrodynamic modes are evaluated as an expansion in the momentum vector. The shear-rate dependence and anisotropy of the transverse and longitudinal velocity correlations are analyzed. We demonstrate that hydrodynamic correlations in shear flow are anisotropic, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 42 publications
1
21
0
Order By: Relevance
“…[8], using fluctuating hydrodynamics calculations, the correlations in hydrodynamic fluctuations in a sheared fluid were evaluated for small wave vectors and arbitrary shear rates. It was shown that the temporal decay of the velocity and density fluctuations in shear flow are anisotropic and shear-rate dependent, which we recently verified using mesoscopic hydrodynamic simulations [14]. More importantly, the equal-time correlations were predicted to be spatially long-ranged and follow an algebraic decay for unbounded systems.…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…[8], using fluctuating hydrodynamics calculations, the correlations in hydrodynamic fluctuations in a sheared fluid were evaluated for small wave vectors and arbitrary shear rates. It was shown that the temporal decay of the velocity and density fluctuations in shear flow are anisotropic and shear-rate dependent, which we recently verified using mesoscopic hydrodynamic simulations [14]. More importantly, the equal-time correlations were predicted to be spatially long-ranged and follow an algebraic decay for unbounded systems.…”
Section: Introductionsupporting
confidence: 68%
“…In order to maintain an isothermal state under shear, we employ a cell-level Maxwell-Boltzmann rescaling of the relative velocities of the particles [29]. This rescaling method for MPC fluid has been shown to reproduce the isothermal states consistent with the fluctuating Navier-Stokes equations in equilibrium and under shear flow [14,25]. Length and time scales in our simulations are given in terms of the length a of a cubic cell and τ = ma 2 /k B T , where m is the mass of a MPC fluid particle.…”
Section: Simulation Approach a Mpc Simulationsmentioning
confidence: 99%
“…Since the random terms do not contribute in this shear rate regime [26,29], the correlations of the fluctuating variables are readily expressed as Given the values of λ µ , ξ µ and χ µ ,, we find that G ǫι = 0 for ǫ = ι and G ǫι = 0 for ǫ = ι.…”
Section: B Hydrodynamic Matrixmentioning
confidence: 97%
“…By considering moderate shear rateγ < ∼ νk 2 0 , cross correlations may be neglected [25,35,36]. To account for the advection of the shear, let k(t) = (k x , k y −γtk x , k z ) denote the time dependent wave vector and k(t) = |k(t)|.…”
Section: Transversal Autocorrelation Functions Of Fluctuations Imentioning
confidence: 99%
“…(31), (32), and (33) are time-dependent as well. The evolutions of the fluctuating variables in k-space can be solved via the perturbation theory [25] and therefore, the normalized transversal autocorrelation functions (TACFs) read as [36]…”
Section: Transversal Autocorrelation Functions Of Fluctuations Imentioning
confidence: 99%